Multinationals in Latin America Case Studies - Liberman, L.; Garcilazo, S.; Stal, E.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
The book deals with cases about the impact of, and interaction between, the different Latin American cultural, economic, legal, and political settings on activities, strategies, structures and decision-making processes of MNCs. The cases focus on business processes, settings and organizational behavior in Latin America.
Keywords: Leadership; International business enterprises; Management; Industrial management; International economics; Organization; Planning; Business Strategy/Leadership.; International Business; Innovation/Technology Management; Management; International Economics; Organization